Higher education accreditation, quality assurance and their impact to teaching and learning enhancement - Makhoul, Samar Aad (2019)
Purpose This paper aims to study the relationship between higher education accreditation and teaching and learning enhancements in academic institutions. Higher education institutions are now looking at satisfying the standard by standard list assigned by internationally recognized accreditation agencies. The purpose of this paper is to investigate whether outside quality confirmation can truly influence the inward life of higher education institutions. Will accreditation implementation have an impact on teaching and learning enhancement and drive institution change? Design/methodology/approach This study was based on an explanatory qualitative design whereby individual faculty members who are tenured or in tenure-track positions in business schools in Lebanese universities were interviewed. The latter universities from which interviewees were questioned are either the Association to Advance Collegiate Schools of Business (AACSB) accredited or currently pursuing accreditation. The sample included 30 faculty members from four different higher education Lebanese institutions. Findings Following thorough review of previous literature, and building on the outcomes of the interviews conducted for the purpose of this research, the author deduced that AACSB serves as the optimal guiding mechanism that incorporates effective evaluation criteria for learning quality and universities. There also exist a lack of commonality and shared standards among accrediting agencies. The researchers also highlight the need to introduce further quantification into the accrediting measures adopted including faculty retention and student attrition rates. Research limitations/implications Ranking agencies were not considered in this study. Those can be used to assess the effectiveness of higher education institutions and will provide fair quality assurance of learning. It is encouraged to incorporate the ranking agencies variable within the scope of future studies for further analysis. Practical implications The paper includes the need to introduce further quantification into the accrediting measures adopted including faculty retention and student attrition rates. Originality/value The focus of this study will be of particular interest to Business school seeking or maintaining accreditation. It will also be of interest to the Lebanese government if they want to look at having a regional accreditation. Future research could possibly explore the need to have a regional accreditation especially with the emerging numbers of higher education institutions in Lebanon.